Pemenuhan Hak Alimentasi Bagi Lansia di Masa Pandemi Covid-19 (Studi di Kedungkelor Wanureja Tegal): Fulfillment of Alimentation Rights for the Elderly During the Covid-19 Pandemic (Study at Kedungkelor Wanureja Tegal) - Waspiah, Waspiah; Arifin, Ridwan; Latifiani, Dian; Rodiyah, Rodiyah; Cahyani, Kartika Fajar; Widiastuti, Anita Indah; Pratiwi, Adinda Ratna; Ayu, Adelya Setya (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
Indonesia's demographic bonus from various studies and analyzes shows various potentials for the development of young people, but in the second phase of the demographic bonus, the elderly population is predicted to increase significantly. The peak of the demographic bonus enjoyed by Indonesia, from various government data and expert research is estimated to occur in 2028-2031. After that, the number of elderly people will grow. The increasing number of elderly population has the potential to provide many benefits if they are strong, healthy and remain productive. However, keeping the elderly population healthy, resilient and productive certainly requires a lot of preparation and support from all parties. Issues of nutritional quality, sanitation and support for a healthy environment have become a number of priorities that must be realized, as is the preparation of the quality of the productive age population. Even the National Institute on Aging (NIA) underlines that elderly people are the fastest growing proportion of the world's population. People are living more advanced, but that does not mean they are healthier. The increase in the aging population brings with it many opportunities but also a number of public health challenges that we need to prepare for. One of the challenges faced is the problem of health and poverty. In fact, according to research by the Center for Aging Society (CAS) of the University of Indonesia, based on BPS data in 2019, the number of elderly people in Indonesia has reached 25 million people. The majority of the elderly live in villages which generally have low education or only elementary school. He also noted that there were around 2.4 million elderly people who were neglected. This service program is intended to increase understanding of the right of alienation for the elderly in Kedungkelor Tegal Village by collaborating with the Kedungkelor Tegal Elderly Healthy House (RUSELA) partner. This service program is expected to not only increase the understanding of the rights of the elderly, but also increase family awareness in maintaining both mental and physical health of parents, and also as a form of responsibility for a child. This program is expected to be able to encourage positive behavior of children towards their parents and be able to improve the welfare of the elderly.